HUBUNGAN KEMAMPUAN LITERASI INFORMASI MENGENAI KEHAMILAN DENGAN TINGKAT KECEMASAN PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS KECAMATAN CIPUTAT - Jihan Almira Dewi (2022)
Pregnant woman has become individu that needs a lot of information, moreover in this digital era when information can found through online sources. To find and filter the information needed through online media can be called information literacy skills. When a woman experiences pregnancy, there are physiologist and psychologist changes that can have several impacts on mother. This study focuses on the psychologist impact of pregnant woman, anxiety. The purpose of this study is to see the correlation between information literacy skills regarding pregnancy and anxiety levels in pregnant woman in the working area of Puskesmas Kecamatan Ciputat. The research method of this study is descriptive analytic cross sectional. The sampling technique used a total sampling with 106 respondent. The instrument that this study used for information literacy skills is a modification questionnaire from the Ministry of Communication and Informatics with total 11 questions, and this study used Pregnancy Related Anxiety Questionnaire Revised 2 (PRAQ-r2) to measured anxiety levels with total 10 questions, both of the questionnaire has been tested for validity and reliability. The results of the analysis using chi square test showed a p-value of 0,006, which means that there is correlation between information literacy skills and anxiety levels in pregnant women. It is recommended that pregnant women can seek information about pregnancy problems as one of the mother's efforts to reduce anxiety, but the information must be re-examined for its veracity by asking health professionals directly or reading information through online media such as officially licensed applications.